异齿数下齿轮泵困油与卸荷的面积计算 - 李玉龙; 刘焜 (Jixie chuandong)
With length of action of driving gear as a variable and the method of sweep volume,the corresponding formula of trapped area and relief area and their change with length of action in different number of teeth between driving gear and driven gear are derived.The foundation of trapped oil pressure simulation is laid.Finally,the influence of different number of teeth on trapped area and relief area in an example is analyzed,and some important conclusions are deduced.